Energy and nutrient supply in school lunches served in selected kindergartens/schools in Henan province, 2021–2023: a cross-sectional survey - Lifeng ZHANG; Yongheng SU; Ruichun YANG; Xie WANG; Ruiling LIANG (Zhongguo gonggong weisheng)
ObjectiveTo assess the energy and nutrient content in school lunches served in kindergartens/schools in Henan province and to provide evidence for improving the nutritional quality of student meals. MethodsFrom 2021 to 2023, a total of 240 school lunch food samples were randomly selected from 16 kindergartens, 16 primary schools and 16 secondary schools in three cities in Henan Province on consecutive 5 days. The nutrient content of the food samples was determined by chemical analysis methods according to relevant national standards. The nutritional evaluation was conducted with reference to the "Nutritional Guidelines for Student Meals" and the "Dietary Nutrient Reference Intakes for Chinese Residents. ResultsThe energy supply (kJ) of the samples for kindergarten, elementary school, and junior high school students was 1979.4, 2 665.2, and 3 056.0, respectively, with 67.5%, 50.0%, and 45.0% exceeding the recommended amount by 80%. Protein content (g) was 19.7, 25.6, and 28.2, respectively, with 92.5%, 85.0%, and 85.0% exceeding the recommended amount by 80%. Sodium content (mg) was 1 133.0, 1 488.4, and 1 825.2, respectively, all exceeding the recommended amount. Vitamin A content (μ g) was 50.0, 65.0, and 75.0, with 97.5%, 97.5%, and 100% of the samples being 60% below the recommended amount. Calcium content (mg) was 120.5, 140.9, and 130.5, with 67.5%, 65.0%, and 67.5% of the samples being 60% below the recommended amount; zinc content (mg) was 1. 3, 1.7, and 1.8, with 40.0%, 65.0%, and 67.5% of the samples being 60%below the recommended amount. The ratio of iron supply to the recommended amount was 117.5%, 103.6%, and 63.9%; while the selenium supply was 93.3%, 46.4%, and 28.3% of the recommended amount, respectively. There were significant differences in the compositional ratios of energy, protein, and selenium to the recommended amount among samples from kindergarten, elementary school, and junior high school (all P<0.05). The proportions of energy intake from protein were 18.4%, 15.3%, and 16.0% for the kindergarten, elementary school, and junior high school samples, respectively, which were slightly high. The proportions of energy intake from fat and carbohydrate were adequate. ConclusionsThe nutritional content of school lunches served in some kindergartens and schools in Henan province was unbalanced, and the content of some nutrients differed significantly from the recommended amount, suggesting that guidance on the nutritional balance of school lunches should be strengthened.